Electrode montage for transcranial direct current stimulation governs its effect on symptoms and functionality in schizophrenia - Yamada, Yuji; Narita, Zui; Inagawa, Takuma; Yokoi, Yuma; Hirabayashi, Naotsugu; Shirama, Aya; Sueyoshi, Kazuki; Sumiyoshi, Tomiki (Frontiers in Psychiatry, 2023)
Backgrounds: Patients with schizophrenia suffer from cognitive impairment that worsens realworld functional outcomes. We previously reported that multi-session transcranial direct current stimulation (tDCS) delivered to the left dorsolateral prefrontal cortex (DLPFC) improved daily living skills, while stimulation on the left superior temporal sulcus (STS) enhanced performance on a test of social cognition in these patients. To examine the regiondependent influence of tDCS on daily-living skills, neurocognition, and psychotic symptoms, this study compared effects of anodal stimulation targeting either of these two brain areas in patients with schizophrenia.: Data were collected from open-label, single-arm trials with anodal electrodes placed over the left DLPFC (N=28) (Narita et al. 2017) or STS (N=15) (Yamada et al. 2022). Dailyliving skills, neurocognition, and psychotic symptoms were measured with the UCSD performance-based skills assessment-brief (UPSA-B), Brief Assessment of Cognition in Schizophrenia (BACS), and Positive and Negative Syndrome Scale (PANSS), respectively.After baseline evaluation, tDCS (2 mA×20 min) were delivered two times per day for 5 consecutive days. One month after the final stimulation, clinical assessments were repeated.Results: Performance on the UPSA-B was significantly improved in patients who received anodal tDCS at the left DLPFC (d = 0.70, p < 0.001), while this effect was absent in patients with anodal electrodes placed on the left STS (d = 0.02, p = 0.939). Significant improvement was also observed for scores on the BACS with anodal tDCS delivered to the DLPFC (d = 0.49, p < 0.001); however, such neurocognitive enhancement was absent when the STS was stimulated (d = 0.05, p = 0.646). Both methods of anodal stimulation showed a significant improvement of General Psychopathology scores on the PANSS (DLPFC, d = 0.50, p = 0.027; STS, d = 0.44, p = 0.001).These results indicate the importance of selecting brain regions as a target for tDCS according to clinical features of individual patients. Anodal stimulation of the left DLPFC may be advantageous in improving higher level functional outcomes in patients with schizophrenia.